Economic burden of neurological disorders in an aging society (Japan): A panel data analysis - Farhad Taghizadeh-Hesary; Naoyuki Yoshino; Aline Mortha; Farzad Taghizadeh-Hesary; Farnaz Roshanmehr; John Fiallos; Erika Tajra; Joe Bolanos; Marco Amaya; Jonathan Dang; Peyman Tashkandi; Vicky Yamamoto; et al. (Asian Development Bank Institute (ADBI), 2020)
Japan's aging population poses a variety of problems, one of which is the increase in neurological disorders. In this study, we propose a framework quantifying the decline in gross domestic product (GDP) resulting from the reduction of labor from two neurological disorders, Alzheimer's disease and strokes. Using panel data from Japanese prefectures between 2001 and 2012, this analysis first estimates the hours of labor lost due to the prevalence of or the informal care associated with the two diseases. This measure gives us an approximation of the total loss of GDP per prefecture due to these neurological disorders. Our findings show that the loss has been decreasing, but remains higher than that estimated using accounting methods. This evolution might be explained by higher values for capital and total factor productivity. In addition, it appears that the GDP of urban prefectures and prefectures relying heavily on tourism are less affected by the labor shortage. The study confirms the importance of investments in research and development (R&D) and capital stock to soften the effects of labor shortages. Nevertheless, given the aging trend in Japan and many other G20 economies, increasing R&D and private capital stock may not prove sustainable in the future.
Keywords: I18; J14; E13; 330; neurological disorders; Alzheimer's disease; stroke; aging population; Japan